Investigation of new layout design concepts of an array-on-device WaveSub device. (May 2022) - Faraggiana, E.; Chapman, J.C.; Williams, A.J.; Whitlam, C.; Masters, I.
Abstract: Wave Energy Converters (WECs) have not yet proven their competitiveness in the mainstream energy market. Research and development of this technology are necessary to find optimal solutions in terms both of energy produced and reduced cost. A WEC farm is expected to have reduced Levelized Cost of Energy (LCoE) compared to individual devices due to shared installation and grid connection costs. Studies show that energy yield of a WEC array is highly dependent on spacing and layout of the WECs. A method for selecting an optimal array layout is desirable. Here we show a comparison between 4 different design layouts of a WaveSub device with six floats. A six float configuration has been chosen because the LCoE reduces with increasing floats per device as shown in previous research. An optimal configuration in terms of LCoE and rated power is found for linear, rectangle, triangle and circular multi-float configurations. Parameters optimised are float spacing and Power Take Off (PTO) stiffness, damping and rated power. The optimisation algorithm uses a genetic algorithm combined with a Kriging surrogate model. Numerical simulations are solved in the time-domain in WEC-Sim while the hydrodynamic coefficients are calculated in Nemoh using a linear potential flow theory. For all geometric configurations, the smallest float spacing was the most promising because of the lower cost of the structure. In fact, the influence of the float spacing on the power produced by the device is shown to be less significant than the influence of float spacing on the capital cost. Overall, the circular configuration outperformed the other configurations. This study shows that layout configurations can be investigated with optimisation and this could be applied to other configurations and other WEC concepts in future.